(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article explores the linguistic and translational aspects of lexical neologisms emerging in online mass media discourse under the influence of globalization, technological advancement, and innovation-driven processes. The study examines not only the structural and functional characteristics of neologisms, but also their pragmatic features, arguing that their rapid formation and widespread dissemination constitute a significant indicator of contemporary language development. The findings of the research demonstrate that such translation techniques as transliteration, transcription, calque, descriptive translation, and substitution with an equivalent lexical unit are widely employed in rendering neologisms into Uzbek. These methods are illustrated through relevant examples, with particular attention paid to the conditions of their application and their relative effectiveness. The study concludes that preserving semantic accuracy, considering cultural context, and ensuring comprehensibility for the target audience are the principal criteria in the translation of neologisms in internet media discourse.